(untitled) (International Journal of Physiotherapy, 2015)
Background: The most critical feature of motor development is the ability to balance the body in sitting or standing. Impaired balance limits a child’s ability to recover from unexpected threats to stability. The functional reach test (FRT) defines the maximal distance an individual is able to reach forward beyond arm’s length in a standing position without loss of balance, taking a step, or touching the wall. The Purpose of this study was to establish the normal values for FRT in Saudi Arabia school children with typical development and to study the correlation of anthropometric measures with FRT values. Methods: This cross-sectional study was conducted in Almadinah Almonawarah, Kingdom of Saudi Arabia. A total of 280 children without disabilities aged 6 to 12 years were randomly selected. Functional reach was assessed by having subjects extend their arms to 90 degrees and reach as far forward as they could without taking a step. Reach distance was recorded by noting the beginning and final position of the subject’s extended arm parallel to a yard stick attached to the wall. Three successive trials of FRT were performed and the mean of the three trials was calculated. Pearson product moment correlation was used to examine the association of FR to age, and anthropometric measures. Results: Normal mean values of FR ranged from 24.2cm to 33.95cm. Age, height and weight significantly correlate with FRT. Conclusion: The FRT is a feasible test to examine the balance of 6-12 year-old children. FRT may be useful for detecting balance impairment, change in balance performance over time.